(untitled) (Journal of Medical & Health Sciences Review, 2025)
This study aimed to evaluate the prevalence of malaria due to Plasmodium species among pregnant women at Mardan Medical Complex. A total of 250 blood samples were collected from pregnant women presenting with clinical symptoms including fever, chills, vomiting, and headache. Diagnostic assessments utilized both microscopy and rapid diagnostic tests (RDTs) to detect specific Plasmodium species. Out of the samples analyzed, 65 (26%) tested positive for malaria, while 185 (74%) were negative. Among the positive cases, 58 (23.2%) were identified as P. vivax, 6 (2.4%) as P. falciparum, and 1 (0.4%) showed mixed infection with both P. vivax and P. falciparum. Statistical analysis indicated a significant correlation between malaria infection and the presence of clinical symptoms, with a p-value of less than 0.005, highlighting the considerable burden of malaria in this demographic. The findings underscore the need for enhanced malaria control strategies to mitigate the risks associated with malaria during pregnancy. This study contributes to the understanding of malaria prevalence in pregnant populations and emphasizes the importance of targeted interventions.